Technical advances in endoscopic ultrasound-guided fiducial placement for the treatment of pancreatic cancer - Chavalitdhamrong, Disaya; DiMaio, Christopher J.; Siersema, Peter D.; Wagh, Mihir S. (Endoscopy International Open, 2015)
Radiation therapy has an important role in the treatment of locally advanced or metastatic pancreatic cancer and can be used alone or in conjunction with surgery and/or systemic chemotherapy. Because of the challenge of delivering an accurate and optimal radiation dose, image-guided radiation therapy can be used to improve targeting. Fiducial markers can be placed in the tumor and used for localization in patients undergoing image-guided radiation therapy. The safety and feasibility of endoscopic ultrasound (EUS)-guided placement of fiducials has been assessed and reported for the management of pancreatic cancer. We herein review the technique, efficacy, and safety profile of EUS-guided fiducial placement. In addition, we highlight recent advances and technological upgrades in EUS-guided fiducial delivery systems for pancreatic cancer most relevant to practicing gastroenterologists and interventional endoscopists.